Water Treatment Effectiveness at the Refilling Drinking Water Station in Ternate on Water Quality Based on Physical, Chemical, and Biological Parameters - Badrun Ahmad; Muhammad Taufiq Y.S (Poltekkes Kemenkes Surabaya, 2025)
Safe drinking water is a primary necessity for life. This study aims to evaluate the effectiveness of water treatment at the Refilling Drinking Water Station in Ternate using the non-parametric Man Whitney technique to analyze the difference in water quality before and after treatment. The method used was quantitative descriptive, with data collected from 20 water samples (10 before and 10 after treatment), with parameters tested including physical, chemical, and biological aspects. The results showed that the physical parameters met quality standards. The chemical parameters indicated that Cr(VI) levels in well water exceeded the quality standard, while biological parameters recorded a significant decrease in coliform bacteria and E. coli after treatment. The conclusion of this study suggests that the water treatment at Drinking Water Refill Station Ternate is effective in improving water quality, making it safe for consumption, though more attention is needed regarding the Cr(VI) content, which remains high in some samples.